2012
DOI: 10.4103/0975-7406.100287
|View full text |Cite
|
Sign up to set email alerts
|

Significance of curve of Spee: An orthodontic review

Abstract: Exaggerated curve of Spee is frequently observed in dental malocclusions with deep overbites. Such excessive curve of Spee alters the muscle imbalance, ultimately leading to the improper functional occlusion. It has been proposed that an imbalance between the anterior and the posterior components of occlusal force can cause the lower incisors to overerupt, the premolars to infraerupt, and the lower molars to be mesially inclined. This altered condition requires specialized skills for the practitioner. It would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…Recent research has revealed that it had a curvature that extends from the centre teeth’s incisor edges to their distobuccal cusps [ 3 ]. The literature claims that the mesial inclination of the lower molar teeth’s long axis caused the masticatory muscles to function improperly, which led to the development of the COS [ 4 , 5 , 6 ]. One study suggested that the Curve of Spee may play a biomechanical role in the processing of food by enhancing the crush/shear ratio between the posterior teeth and the efficiency of occlusal pressures during the masticatory process [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has revealed that it had a curvature that extends from the centre teeth’s incisor edges to their distobuccal cusps [ 3 ]. The literature claims that the mesial inclination of the lower molar teeth’s long axis caused the masticatory muscles to function improperly, which led to the development of the COS [ 4 , 5 , 6 ]. One study suggested that the Curve of Spee may play a biomechanical role in the processing of food by enhancing the crush/shear ratio between the posterior teeth and the efficiency of occlusal pressures during the masticatory process [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature claims that the mesial inclination of the lower molar teeth’s long axis caused the masticatory muscles to function improperly, which led to the development of the COS [ 4 , 5 , 6 ]. One study suggested that the Curve of Spee may play a biomechanical role in the processing of food by enhancing the crush/shear ratio between the posterior teeth and the efficiency of occlusal pressures during the masticatory process [ 4 ]. This suggestion alluded to the idea of “masticatory efficiency.” The COS permits unrestricted lower jaw motions while enhancing food chewing by maintaining upper and lower tooth contacts throughout operation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This tilt of the curve of Spee increases the crush/shear ratio of the force produced on food between the posterior molars (24). In addition, the concave border of anterior ramus favors the development of compression and tension loads during mastication.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the side effects of using these unchecked materials would be proclination of the anterior teeth, lingual or distal tipping of the molars etc. [ 28 ]. In case of aligners, the curve of Spee is flattened by extrusion of premolars and molars using extrusive attachments or by intruding the anteriors using intrusive attachments [ 13 ].…”
Section: Why Clear Aligners?mentioning
confidence: 99%